Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Number Head Together di Kelas V Sekolah Dasar - Serlli Yulita; Rifda Eliyasni (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The study aims to describe the increased learning outcomes of integrated thematic learning using NHT-type cooperative learning models in elementary school V-grade. This research is a class action research with a Model NHT type can improve the results of integrated thematic learning in class V SDN 16 Tarok Dipo qualitative and quantitative approach to the subject of this study is teacher and 22 students. The study was conducted in 2 cycles, I conducted 2 × cycle meetings, and the II cycle consisted of 1 meeting time. Through the implementation of the NHT type Cooperative learning Model, student learning outcomes experienced an increase from cycle 1 to cycle II i.e., 64% in I cycles increased to 91% in cycle II. Based on the results of the discussion and analysis can be concluded that the application of cooperative learning